Piero Manzoni’s “Merda d’artista”. Psychoanalytic interpretations and side effects - Pasquale Fameli (PsicoArt, 2018)
This paper focuses on the critical analysis of Merda d’artista (1961) by Piero Manzoni, underlining the problematic nature of psychoanalytic interpretations proposed by Nancy Spector, Jean-Pierre Criqui, Gerard Silk and others related to Freudian theories. Starting from the philosophical interests of the artist and his theoretical declarations, it proposes a reinterpretation of the famous Manzoni’s work in the perspective of that bond to the social and experiential dynamics that will characterize most of the conceptual researches of the late Sixties.